Riding the nightmare : a Duff MacCallister western - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. MacCallister, the eagles legacy (Series), 2022)
"Duff MacCallister left Scotland to forge a new life in America, raising cattle on the western plains of the growing nation. But keeping his dream alive means facing off against the country's most violent, bloodthirsty men ... The Spencer family is part of a wagon train passing through Chugwater, Wyoming, bound for the valley of Longshot Basin. Unfortunately, the trail that leads there has been buried under an avalanche. The only route the homesteaders can take is the infamous Nightmare Trail-a treacherous, terrifyingly steep and narrow mountainside path that has claimed many lives. If that wasn't dangerous enough, the trail is also a killing ground for the outlaw Hardcastle gang. The disreputable Arkansas Ozark clan don't take kindly to anyone trespassing on their road without paying-in blood. Duff MacCallister is not about to let the Spencers ride the Nightmare Trail without his guidance. He knows the terrain. He knows how to defend himself. And he knows that when it comes to badmen like the Hardcastles, the best defense is killing first-and fast" --